2008
DOI: 10.1007/s00192-008-0718-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rate and risk factors for vaginal vault prolapse repair after hysterectomy

Abstract: Our objective was to estimate the incidence and identify the risk factors for vaginal vault prolapse repair after hysterectomy. We conducted a case control study among 6,214 women who underwent hysterectomy from 1982 to 2002. Cases (n=32) were women who required vaginal vault suspension following the hysterectomy through December 2005. Controls (n=236) were women, randomly selected from the same cohort, who did not require pelvic organ prolapse surgery. The incidence of vaginal vault prolapse repair was 0.36 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 16 publications
(28 reference statements)
0
38
0
2
Order By: Relevance
“…Studies of prolapse after vaginal hysterectomy indicate a low rate for this complication, which occurs when pelvic floor tissues are weak preoperatively [18]. After transvaginal NOTES, because the colpotomy is performed in the posterior fornix, the uterine suspensory ligaments (apical support) remain unaffected by the procedure, so the incidence of prolapse (hernia) likely is low.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of prolapse after vaginal hysterectomy indicate a low rate for this complication, which occurs when pelvic floor tissues are weak preoperatively [18]. After transvaginal NOTES, because the colpotomy is performed in the posterior fornix, the uterine suspensory ligaments (apical support) remain unaffected by the procedure, so the incidence of prolapse (hernia) likely is low.…”
Section: Discussionmentioning
confidence: 99%
“…However, hysterectomy removes a healthy, albeit poorly supported organ. It fails to tackle pathological connective tissue weakness, primarily the uterosacral and cardinal ligaments, and this contributes to the subsequent high apical prolapse rates seen with this operation [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that vaginal hysterectomy is not a risk factor for pelvic organ prolapse repair or vaginal vault prolapse repair when preoperative prolapse is taken into account. Grade 2 or more preoperative prolapse was significantly associated with reoperation [13,14]. However, we preferred supracervical or subtotal hysterectomy to total hysterectomy.…”
Section: Discussionmentioning
confidence: 96%